2016
DOI: 10.5465/amj.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

The Online Shadow of Offline Signals: Which Sellers Get Contacted in Online B2B Marketplaces?

Abstract: Abstract:This article extends the understanding of what impels buyers to contact particular sellers in online business-to-business (B2B) marketplaces, which are typically characterized by sparse social structures and concomitant limitations in observing social cues. Integrating an institutional perspective with signaling theory, our core argument is that offline seller characteristics that are visible online-in particular, geographic location and legal statusconvey credible signals of seller behavior because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 96 publications
(96 reference statements)
2
43
0
1
Order By: Relevance
“…Research indicates that to overcome some of the information asymmetry in B2B markets, buyers are likely to rely on signals that are either generated by the supplier -intentional signals, or by the market -unintentional signals, to shortlist and engage with suppliers in online B2B markets (Lanzolla and Frankort, 2016). As many suppliers provide the same intentional signals, studying how buyers are influenced by unintentional signals such as those generated by social media feedback presents both theoretical and practical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that to overcome some of the information asymmetry in B2B markets, buyers are likely to rely on signals that are either generated by the supplier -intentional signals, or by the market -unintentional signals, to shortlist and engage with suppliers in online B2B markets (Lanzolla and Frankort, 2016). As many suppliers provide the same intentional signals, studying how buyers are influenced by unintentional signals such as those generated by social media feedback presents both theoretical and practical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The transaction value in these markets is also substantially different. Buyers in B2B markets typically engage in much higher value transactions -therefore both the trading risk and value appropriation risk are much higher compared to B2C transactions (Lanzolla and Frankort, 2016).…”
Section: Signalling Theory In B2b Marketsmentioning
confidence: 99%
“…In addition to the Lanzolla and Frankort (2016) suggested study, which we appreciate, we also now cite Almazan, DeMotta, Titman and Uysal (2010) who describes the increased formation of acquisitions with clustered firms. To provide more specific evidence relevant to our context, we now mention Folta, Cooper, and Baik (2006) who provide evidence of the higher levels of partnering with firms located in biotechnology clusters and Coombs, Mudambi and Deeds (2006) who show that the technological munificence of a biotechnology firm's region plays an important role in attracting alliance capital from corporate partners.…”
Section: Responsementioning
confidence: 74%
“…For instance, Jaffe et al (1993) Forming relationships with firms in clusters has been suggested as a way for isolated firms to access the benefits of clusters (McCann & Folta, 2008). Empirical research has indicated that clustered firms are involved in more acquisitions (Almazan, DeMotta, Titman & Uysal, 2010) and are targeted more frequently in online B2B markets (Lanzolla & Frankort, 2016). Both Rothaermel (2002) and Folta, Cooper, and Baik (2006) provided similar evidence of the higher levels of partnering with firms located in biotechnology clusters, just as Coombs, Mudambi and Deeds (2006) showed that the technological munificence of a biotechnology firm's region plays an important role in attracting alliance capital from corporate partners.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We excluded studies that study market exchanges/spot sourcing relationships between two organizations (see e.g. Lanzolla and Frankort, 2016) as these are not structural agreements. We also excluded buyer-supplier relationships and board interlocks, because the interdependence and amount of resource control is lower in these interorganizational arrangements as compared to e.g.…”
Section: Inclusion Criteriamentioning
confidence: 99%